2020
DOI: 10.1002/nse2.20011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multimedia learning tools in agricultural science classes

Abstract: Agricultural and environmental scientists collaborated with educational technology researchers to create multimedia learning tools to fill gaps in student understanding of key concepts that undergraduates often struggle with, including sorption, cation exchange capacity, inner and outer sphere bonding, and soil system complexity. These resources are freely available online at ScienceOf-Agriculture.org. The modules were evaluated in several soil, environmental science, and agriculture classes using pre-and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The design process used to create many of the SoA, UWS, and VL activities has also been shown to be highly effective (Mayo, 2007;Foster, 2008;Chamberlin et al, 2012). Furthermore, specific activities within the SoA website have been evaluated and demonstrated to enhance student learning (Ulery et al, 2020). Some concepts such as CEC or sorption are more easily visualized using computer graphics and online tools (Ulery et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The design process used to create many of the SoA, UWS, and VL activities has also been shown to be highly effective (Mayo, 2007;Foster, 2008;Chamberlin et al, 2012). Furthermore, specific activities within the SoA website have been evaluated and demonstrated to enhance student learning (Ulery et al, 2020). Some concepts such as CEC or sorption are more easily visualized using computer graphics and online tools (Ulery et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several of the SoA activities were well aligned with the lecture topics remaining in SOIL 210 at the time of the shift to distance learning ( Figure 1). Another important consideration was that previous research indicated that the SoA activities were successful in helping students grasp difficult soil science concepts (Ulery et al, 2020). Therefore, SoA was chosen for the development of several online laboratory activities for the second half of the semester.…”
Section: The Decisionmentioning
confidence: 99%
See 2 more Smart Citations
“…This special section contains 12 articles that illustrate a range of philosophies, techniques, teaching methods, and/or case studies developed to enhance undergraduate and graduate education in natural sciences at 11 universities in the United States and Canada. Reflecting the ongoing trend of incorporation of online educational tools to enrich campus‐based courses, several articles describe development of some of those online tools (Culbert, 2020; Ulery et al., 2020). A group of articles in this special section focus on the experiential learning and enhancement of student engagement.…”
mentioning
confidence: 99%